Nuevas técnicas terapéuticas de contra-condicionamiento: Conciencia de la pie y visceral - Navarro, Roberto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study investigated possible differences between the Techniques of Skin Consciousness, Visceral Awareness, and Wolpe’s Muscular Relaxation. These Techniques were presented to three groups of students (twelve females in each group), who were asked to rate each Technique with eleven Scales. Data were analyzed with ANOVA (3x3, with three Technique levels and three Order levels).